Persistent GeV Counterpart to the Microquasar GRS 1915+105 - Guillem Martí-Devesa; Laura Olivera-Nieto (The Astrophysical Journal Letters)
Microquasars are compact binary systems hosting collimated relativistic jets. They have long been proposed as cosmic-ray accelerators, probed via the gamma-ray emission produced by relativistic particles. However, the observational evidence is steadily increasing but limited: there are around 20 microquasars known to date, of which only 3 have so far been firmly detected in the GeV gamma-ray range, always in a flaring or special spectral state. Here we present Fermi-LAT observations of the region around the microquasar GRS 1915+105, which reveal the presence of previously unknown multi-GeV emission consistent with the position of the microquasar. No periodicity or variability is found, indicating a persistent source of gamma rays. The properties of the emission are consistent with a scenario in which protons accelerated in the jets interact with nearby gas and produce gamma rays. We find that if the jet has been operating at an average of 1% of the Eddington limit for 10% of the time that GRS 1915+105 spent in its current mass transfer state, the transfer of 10% of the available power to protons is enough to reach the ∼3 × 10 ^49 erg required to explain the GeV signal. Therefore, our results support a scenario in which microquasars with low-mass stellar companions act as hadronic accelerators, strengthening the idea that microquasars as a class contribute to at least some fraction of the observed cosmic-ray flux.